Pengaruh Likuiditas dan Kualitas Aset terhadap Nilai Perusahaan dengan Kinerja Keuangan sebagai Variabel Intervening - Kevin Khair Al-Hakim (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to analyze the effect of liquidity and asset quality on firm value, with financial performance as an intervening variable, in food and beverage manufacturing companies listed on the Indonesia Stock Exchange for the 2020-2024 period. The study population included all food and beverage companies, with purposive sampling based on specific criteria. The analytical methods used included multiple linear regression and mediation analysis. The results show that liquidity has no effect on financial performance, while asset quality has no effect on financial performance. Liquidity does affect firm value. Asset quality does not affect firm value. Financial performance does not affect firm value. Liquidity does not mediate the effect on firm value through financial performance, and asset quality does not mediate the effect on firm value through financial performance. These results provide important implications for management and investors in long-term financial planning for companies in the future of the industry.